SITUATION AND SOME RELATED FACTORS OF PHYSICAL ACTIVITIES AMONG ADUTLS IN PHAN DINH PHUNG WARD, THAI NGUYEN CITY IN 2019 (Vietnam Journal of Community Medicine, 2021)
Objective: To describe the situation and some related factors of physical activity among adults inPhan Dinh Phung ward, Thai Nguyen city in 2019.Method: a cross-sectional descriptive studies was conducted on 495 adults in Phan Dinh Phungward, Thai Nguyen city. Data were collected by face-to-face interview using global physical activityquestionnaire (GPAQ).Results: The rate of high-level physical activity in men was 62.1% and for women was 47.8%, with43.8% of women and 62.1% of men achieving physical activity according to WHO recommendations.Age, location convenience, status of hypertension, diabetes, and cardiovascular disease weresignificant related factors of physical activity.
Keywords: Adults, physical activity, related factors